THE EFFECT OF PARTICIPATORY LEADERSHIP STYLE ON EMPLOYEE MOTIVATION ON THE BILLER SECTION (STUDY AT PT. PARSINTAULI KARYA PERKASA GARUT) - Adryan Septiady; Nisa Alghatia (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Abstract This research is motivated by a decrease in the work motivation of employees of PT. Parsintauli Karya Perkasa in 2019-2020. In an organization employees play an important role so that every organizational leader must have the best leadership style for his employees so that these employees have high work motivation. This study aims to determine participatory leadership style, employee work motivation, and the influence of participatory leadership style on employee motivation at PT. Parsindauli Karya Perkasa. The research method used is descriptive and causal associative research methods. Respondents taken in this study were employees of PT. Parsindauli Karya Perkasa, ie 58 respondents. Then processed using validity test, reliability test, correlation test, and coefficient of determination test. Participatory Leadership Style at PT. Parsintauli Karya Perkasa is in good category. And Employee Work Motivation at PT. Parsintauli Karya Perkasa is in good category. Participative Leadership Style (X) has a positive and significant effect on Employee Work Motivation (Y) at PT. Parsintauli Karya Perkasa, with a correlation coefficient of 0.757 means that it has a "strong" influence. While the results of the coefficient of determination of 57.3% and the remaining 42.7% is influenced by other factors outside the variables studied. Keywords: Participatory Leadership Style, Work Motivation